2022
DOI: 10.1111/imj.15098
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study on the epidemiology of antineutrophil cytoplasmic autoantibodies‐associated vasculitis in two Australian health districts

Abstract: Background Antineutrophil cytoplasmic autoantibodies (ANCA)‐associated vasculitis (AAV) is more prevalent in rural Australia compared with metropolitan areas, suggesting a role of environment in disease pathogenesis. However, the prevalence of environmental risk factors in Australian AAV patients has not been described. Aims To compare the incidence of AAV between two health districts (Illawarra Shoalhaven Local Health District (ISLHD), a mixed rural/metropolitan region, and South Eastern Sydney Local Health D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 28 publications
2
3
1
Order By: Relevance
“…This study does not clearly suggest that rural and regional Victoria have a greater incidence of AAV than urban Australian areas. Our overall disease incidence was higher than that described in central Sydney (6 per million/year, 95% CI: 1.9–13.9) 5 ; however, it was lower than that reported in Melbourne between 2009 and 2011 (22 per million/year) 9 . Our estimate was similar to the incidence in urban WA (10.1 per million/year, 95% CI: 7.6–13.8) 8 and the ACT (10.5 per million/year) 6 .…”
Section: Discussioncontrasting
confidence: 83%
See 3 more Smart Citations
“…This study does not clearly suggest that rural and regional Victoria have a greater incidence of AAV than urban Australian areas. Our overall disease incidence was higher than that described in central Sydney (6 per million/year, 95% CI: 1.9–13.9) 5 ; however, it was lower than that reported in Melbourne between 2009 and 2011 (22 per million/year) 9 . Our estimate was similar to the incidence in urban WA (10.1 per million/year, 95% CI: 7.6–13.8) 8 and the ACT (10.5 per million/year) 6 .…”
Section: Discussioncontrasting
confidence: 83%
“…In Australia, a higher incidence of AAV has been reported in rural compared to urban areas. 5,6 Similar findings have also been described internationally in Scotland 10 and Canada. 11 Increased environmental exposure to farming and agents such as silica has been postulated as an explanation for a relationship between rurality and AAV.…”
Section: Introductionsupporting
confidence: 85%
See 2 more Smart Citations
“…Studies in Scotland, Germany, and Canada showed that the incidence of AAV in rural areas is higher than that in cities. This may be related to environmental pollutants and pesticide exposure in remote areas (68,72,78,79). Additionally, a large Swedish case-control study (73) found no association between occupation and GPA (Table 1).…”
Section: Air Pollutionmentioning
confidence: 99%